PENINGKATAN KUALITAS PRODUK MELALUI IbM KELOMPOK USAHA KECIL JAMU TRADISIONAL DI KECAMATAN SAMPANG - Siti Mujanah; Achmad Maqsudi; Rudi Santoso (JPM17: Jurnal Pengabdian Masyarakat, 2015)
Herbal medicine from Madura Island, East Java Province has been known for a long time. Aside from being a medicine, herbs are also often drink as fresh healthy beverage, especially herbal carrying, but the problem of carrying medicinal is perishable product, which only survive within a day so that if it is not sale will be discarded. One of central medicinal to be developed "Putri Pahlawan" which has about 18 members who require assistance in improving the product in order to compete with other medicinal products. This Community services activities was done by providing assistance in the field of improving the quality of production, the application of appropriate technology, marketing training and financial bookkeeping. The results achieved that the 18 members of the group Small Medium Industrial (SMIs) â€œPutri Pahlawanâ€ consists of nine (9) SMIs carrying medicinal have received Cup Sealer for packing herbs carry for easy marketed in stores and 9 (nine) SMIs Herbal medicine packaging, have been received tool Inpulse Sealer, besides that they have also been given training to make herb with good taste nutritious, hygienes and durable, able to package their products with better and highly competitive, able to market products and conduct financial accounting properly.Keywords: Improved product quality, Appropriate Technology, and Marketing